Emerging two-dimensional tellurides. (December 2021) - Siddique, Saif; Chowde Gowda, Chinmayee; Demiss, Solomon; Tromer, Raphael; Paul, Sourav; Sadasivuni, Kishor Kumar; Olu, Emmanuel Femi; Chandra, Amreesh; Kochat, Vidya; Galvão, Douglas S.; Kumbhakar, Partha; Mishra, Rohan; et al.
Graphical abstract: Abstract: Two-dimensional (2D) materials are at the forefront of current materials research due to their exciting and unique properties. 2D tellurides are emerging materials which are yet to be fully explored. To provide an overview of this emergent field, in this review, we discuss the structure, properties, synthesis methods, and applications of selected 2D tellurides, with stoichiometry of Mx Te y, and Mx Ny Te z, ( M, N are metal atoms) . We present a summary of the latest advances in modeling, experimental synthesis, and characterization of 2D tellurides. Additionally, stress and strain-induced tunability of the physical properties have been reviewed, with a focus on the application of 2D tellurides in electronic, optoelectronic, and magnetic devices. We have discussed many emergent quantum properties of these materials. Finally, we conclude with a perspective on the future of 2D metal tellurides.